A judicialização da saúde pública no brasil sob o prisma constitucional - Soares, Cicero de Assis (2021)
The lack of implementation of public policies for the realization of fundamental social rights, as well as the lack of maintenance of the existing ones, has led to the interference of the Judiciary in the Public Administration. In this context, the present research deals with the theme of the study of the right to health guaranteed by the Constitution, which imposes an immediate positive benefit on the part of the State in favor of its recipients. The general objective is to study the issue of health judicialization in Brazil. In turn, the specific objectives are: to analyze the Brazilian constitutional context regarding the right to health as a social right and, therefore, fundamental; to study the Principle of Inafasability of Jurisdictional Control or right of action in relation to the independence of the Powers, in the question of the judicialization of health; and, understand the issue of health judicialization in Brazil. The methodology followed the criteria of the bibliographic research. It was concluded that, given the responsibility of the Public Administration to comply with the constitutional order and the Judiciary, which can not refuse to analyze the postulated social law, the Magistrate can and should produce sentences forcing the Executive to effect a constitutional order in concrete cases. But the Judiciary must also observe the limits imposed by the Corollary of the Separation of Powers, acting in a proportional and reasonable manner.